Influenza A infection with rhabdomyolysis and acute renal failure--a potentially fatal complication. Issue 786 (April 1991) - Berry, L.; Braude, S.
Abstract : This paper describes a case of influenza A infection complicated by rhabdomyolysis and acute renal failure. This very rare complication is particularly important as symptoms may be non-specific and therefore ascribed to the underlying influenzal illness.